Parallax: the dialectics of mind and world - Finkelde, Dominik; Žižek, Slavoj; Menke, Christoph (Bloomsbury Academic, 2021)
Preface: Hegel and the Ethical Parallax, Slavoj Žižek -- Introduction -- Part 1: Parallax in Ontology -- 1. Parallactic Entanglement: On the Subject-Object-Relation in New Materialism and Adorno's Critical Ontology, Dirk Quadflieg (University of Leipzig, Germany) -- 2. Žižek's Parallax, or The Inherent Stupidity of All Philosophical Positions, Graham Harman (SCI-Arc, Los Angeles, USA) -- 3. How Mind fits into Nature. Mental Realism after Nagel, Markus Gabriel (University of Bonn, Germany) -- 4. Parallax in Hermeneutic Realism, Anton Friedrich Koch (University of Heidelberg, Germany) -- 5. Object-Disoriented Ontology. Realism in Psychoanalysis,Alenka Zupancic (Slovenian Academy of Sciences and Arts, Slovenia) -- 6. Temporal Paradox, Realism, and Subjectivity, Paul Livingston (Albuquerque University, USA) -- 7. The Parallactic Leap: Fichte, Apperception, and the Hard Problem of Consciousness, G. Anthony Bruno (Royal Holloway, University of London, UK) -- 8. The Parallax of Ontology: Reality and its Transcendental Supplement, Slavoj Žižek (Birkbeck, University of London, UK) -- Part 2: Parallax in Normative Orders -- 9. Truth as Subjective Effect. Adorno or Hegel, Christoph Menke (Goethe University Frankfurt am Main, Germany) -- 10. Is Sex a Transcendental Category of Parallax? Revisiting the Feminist Second Wave, Nina Power (Roehampton University, UK) -- 11. The Irony of Self-Consciousness: Hegel, Derrida, and the Animal that therefore I am, Thomas Khurana (Yale University, USA) -- 12. A Squinting Gaze on the Parallax Between Spirit and Nature, Frank Ruda (University of Dundee, UK) -- 13. "I am nothing, but I make everything": Marx, Lacan, and the Labor Theory of Suture, Adrian Johnston (University of New Mexico at Albuquerque) -- Part 3: Parallax in Aesthetics -- 14. Drama as Philosophy. The Tragedy of the End of Art, Todd McGowan (University of Vermont, USA) -- 15. Parallaxes of Sinister Enjoyment: The Lessons of Interpassivity and the Contemporary Troubles with Pleasure, Robert Pfaller (University of the Arts, Linz, Austria) -- 16. Whiteheadian Aesthetics: On "Nautical Positionality" from a Process-Ontological Perspective, Eva Schürmann(University of Magdeburg, Germany) -- 17. Feeling at a Distance, or the Aesthetics of Unconscious Transmission, Tracy McNulty (Cornell University, USA) -- 18. The Dream That Knew Too Much. On Freud, Lacan, and Philip K. Dick, Dominik Finkelde (Munich School of Philosophy, Germany) -- Notes on the contributors -- Index of names.
Includes bibliographical references and index
Keywords: Electronic books